Bøger i 1700-tallets nordjyske landsbyskoler - Appel, Charlotte (Fund og Forskning i Det Kongelige Biblioteks Samlinger, 2015)
This article takes its point of departure in a collection of inventories, presented to Bishop Bror Brorson on his visitation journeys in the diocese of Aalborg, Northern Jutland, in the 1750s. The inventories reveal considerable variations: the majority of schools had 3 to 30 books registered, some schools had between 30 and 60 books regisitered, while a minority of schools had no books at all. However, these books were only the tip of the iceberg. By analysing the school decree of 1739 as well as information in the inventories themselves, it can be demonstrated, how parents were responsible for acquiring the necessary teaching materials themselves. The books registered were first of all free copies for poor children, and some of these books were not even listed, as they had been given away to individual children.The inventories bear witness to a high degree of continuity concerning the schoolbooks used for elementary teaching: ABCs, catechisms, gospel books, expositions of the catechism. But it can also be documented that the government had succeeded in introducing Erik Pontoppidan’s new Pietistic exposition of the catechism from 1737 into all village schools. In contrast, there were no central regulations that dealt with teaching materials for writing and mathematics. Instruction in these subjects was a local matter. Moreover, the inventories reveal a number of book donations, especially from Pietistic pastors, and in some cases unique information about the bindings, as well as the wear and tear of schoolbooks can be found. Thus the inventories provide an intriguing window into everyday teaching practices and the role of school books in 18th century village schools.